2020
DOI: 10.1080/19491034.2020.1783782
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of t-loop formation by TRF2

Abstract: T-loops are thought to hide telomeres from DNA damage signaling and DSB repair pathways. Tloop formation requires the shelterin component TRF2, which represses ATM signaling and NHEJ. Here we establish that TRF2 alone, in the absence of other shelterin proteins can form t-loops. Mouse and human cells contain two isoforms of TRF2, one of which is uncharacterized. We show that both isoforms protect telomeres and form t-loops. The isoforms are not cell cycle regulated and t-loops are present in G1, S, and G2. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 43 publications
0
41
0
3
Order By: Relevance
“…During S-phase, TRF2 is transiently dephosphorylated by protein phosphatase 6 regulator subunit 3 (PP6R3), allowing t-loop disassembly and the completion of DNA replication. This t-loop disassembly appears to be very transient and another study suggests that t-loops may be present during S-phase (Timashev and De Lange, 2020). Thus, defining how this switch is regulated, and specifically how the DDR is inhibited during this period, warrants further investigation.…”
Section: Telomeresmentioning
confidence: 98%
“…During S-phase, TRF2 is transiently dephosphorylated by protein phosphatase 6 regulator subunit 3 (PP6R3), allowing t-loop disassembly and the completion of DNA replication. This t-loop disassembly appears to be very transient and another study suggests that t-loops may be present during S-phase (Timashev and De Lange, 2020). Thus, defining how this switch is regulated, and specifically how the DDR is inhibited during this period, warrants further investigation.…”
Section: Telomeresmentioning
confidence: 98%
“…Overexpression of an ectopic allele of RNaseH1 in the TbRAP1depleted cells suppresses the increased amount of telomeric R-loop and DNA damage and the increased VSG switching frequency phenotypes, while the TERRA level in these cells is still higher than that in WT cells (Nanavaty et al, 2017). Therefore, the function of TbRAP1 in maintaining telomere/subtelomere Suppresses NHEJ-mediated chromosome end-to-end fusions van Steensel et al, 1998;Karlseder et al, 1999;Celli and de Lange, 2005 Suppresses telomere HR Wang et al, 2004 Suppresses telomerase-mediated telomere elongation Smogorzewska et al, 2000 Promotes telomeric R-loop formation Lee et al, 2018 Facilitates the T-loop structure formation and maintenance Doksani et al, 2013;Timashev and de Lange, 2020 Suppresses trans-localization of TERRA Feretzaki et al, 2020 The GAR domain is essential for binding TERRA Deng et al, 2009b;Mei et al, 2021 integrity relies on its repressive effects on TERRA and telomeric R-loop. The TERRA molecules in TbRAP1-depleted cells are much longer than that in WT cells (Nanavaty et al, 2017), suggesting that TbRAP1 can block the transcription elongation of RNA Polymerase I along the telomere by associating with the telomere chromatin.…”
Section: Rap1 Homologs In Vertebrates Yeasts and T Bruceimentioning
confidence: 99%
“…Eukaryotic chromosome ends avoid recombination mechanisms through the shelterin mediated formation of the T-loop. T-loop formation is facilitated by the shelterin complex, and most recently it was shown that TRF2 alone is sufficient for this process [1] , [16] , [72] .…”
Section: Pot1 Suppresses Dna Damage Responsementioning
confidence: 99%